HUBUNGAN KETIDAKAMANAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN KONTRAK PADA PT. BANK CIMB NIAGA TBK, WILAYAH BALI - Manuaba, Ida Ayu Ananda Mahadewi; Astiti, Dewi Puri (Jurnal Psikologi Udayana, 2014)
Contract labor system is one of internal changes phenomena in structure and work system that is done by almost every organization including banking industry. The example is Bank CIMB Niaga that uses contract employees in its banking activities. In its development, there are problems in hiring employees by contract system namely the emergence of job insecurity perceived by employees due to career uncertainty at the company. Another problem that arises related to organizational commitment of contract employees. Job insecurity and organizational commitment problem may affect performance of contract employees. This study aims to examine the relationship between job insecurity and organizational commitment with performance of contract employees in PT. Bank CIMB Niaga Tbk, Bali Region. This research is quantitative study using multiple regression data analysis. The population in this study are all contract employees in PT. Bank CIMB Niaga, Bali Region with minimum 1 year working period. The used sampling method is cluster sampling. Respondents in this study are contract employees working in teller and micro division. The number of respondents is 43. Data in this study were obtained by questionnaires and employee performance appraisal data. The result found significant relationship between job insecurity and organizational commitment with performance of contract employees. Job insecurity is negatively related to performance of contract employees. Organizational commitment is positively related to performance of contracts employees. Keywords: employee performance, job insecurity, organizational commitment, contract employee